1996
DOI: 10.1128/aem.62.5.1670-1675.1996
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analyses of Desulfurization of Dibenzothiophene by Rhodococcus erythropolis in Batch and Fed-Batch Cultures

Abstract: The DbtS ؉ phenotype (which confers the ability to oxidize selectively the sulfur atom of dibenzothiophene [DBT] or dibenzothiophene sulfone [DBTO 2 ]) of Rhodococcus erythropolis N1-36 was quantitatively characterized in batch and fed-batch cultures. In flask cultures, production of the desulfurization product, monohydroxybiphenyl (OH-BP), was maximal at pH 6.0, while specific productivity (OH-BP cell ؊1) was maximal at pH 5.5. Quantitative measurements in fermentors (in both batch and fed-batch modes) demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Several literature studies have reported the effect of sulfate on desulfurization activity. Li et al (1996) reported that although sulfate represses the dsz genes, it does not inhibit the activity of desulfurizing enzymes (Wang & Krawiec, 1996). They observed that the desulfurizing activity increased with decreasing amount of sulfate in the medium.…”
Section: Effect Of Sulfate On Desulfurizing Activitymentioning
confidence: 99%
“…Several literature studies have reported the effect of sulfate on desulfurization activity. Li et al (1996) reported that although sulfate represses the dsz genes, it does not inhibit the activity of desulfurizing enzymes (Wang & Krawiec, 1996). They observed that the desulfurizing activity increased with decreasing amount of sulfate in the medium.…”
Section: Effect Of Sulfate On Desulfurizing Activitymentioning
confidence: 99%
“…A biodesulfurization (BDS) process with biocatalyst production followed by biotransformation has been investigated previously. Rhodococcus rhodochrous has been grown in batch, fed batch (5,12,15), and continuous culture (16). DBT degradation was exclusively studied in batch or fed-batch mode (5,12,15).…”
Section: Introductionmentioning
confidence: 99%
“…Rhodococcus rhodochrous has been grown in batch, fed batch (5,12,15), and continuous culture (16). DBT degradation was exclusively studied in batch or fed-batch mode (5,12,15). As a commercial BDS process is likely to be operated continuously, we chose to study the feasibility of conducting the biotransformation reaction in a CSTR.…”
Section: Introductionmentioning
confidence: 99%
“…The desulfurization phenotype of Rhodococcus erythropolis N1-36 (and other bacterial strains [3,8]) has the prospect of being the basis of a metabolically specific, ecologically benign, and economically attractive means of beneficiating fossil fuels (4,11). For a full assessment of the potential of N1-36, such features as maximum specific growth rate ( max ), saturation constant (K s ) (i.e., substrate concentration that yields a growth rate equal to one-half the theoretical maximum), cell yield coefficient (Y x/s ), and temperature dependence (or activation energy) of growth and desulfurization need to be determined.…”
mentioning
confidence: 99%
“…Samples were taken after a steady state was established. During steady-state growth, concentrations of the substrate (DBTO 2 ) and product monohydroxybiphenyl (OH-BP) were determined by high-performance liquid chromatography (9, 10); biomass was estimated by converting culture optical densities to cell dry weights (by using standard curves [9][10][11]).…”
mentioning
confidence: 99%